The first generation of students of the National Academy of Music (1908-1919): analysis from a gender perspective - Botton Becerra, Elena Isabel (2021)
This article intends to carry out an analysis of how gender roles have changed the musical and instrumental preferences of the first students of the National Academy of Music, an institution that paved the way for the professionalization of woman in musical art in a dominance and patriarchal practices context, but also transformations in women’s access to the public sphere. The carrier of those who managed to exercise the musical profession will be revised; likewise, it will be demonstrated how gender roles were reproduced in the educational field, and in a particular way, in a musical institution. The time frame of this research ranges from 1908, the year when the National Academy of Music was created under the protection of an influential Peruvian ruling class attached to the Civil Political Party, until 1919, the year when the mandate of the civilian president José Pardo ended.